Key issues affecting quality of life and patient-reported outcomes in prostate cancer: an analysis conducted in 2128 patients with initial psychometric assessment of the prostate cancer symptom scale (PCSS) - Msaouel, Pavlos (BMJ Support Palliat Care, 2017)
OBJECTIVE: Evidence-based quality of life (QL) questionnaires require the identification of issues of importance to patients. The primary aim of this study was to inform providers on patient-expressed issues while enhancing the content validity of instruments assessing quality of life (QL) and patient reported outcomes (PROs) in prostate cancer. The study provided additional psychometric properties for the new PRO and QL instrument, the Prostate Cancer Symptom Scale (PCSS). METHODS: An anonymous web-based survey of 2128 patients with prostate cancer was conducted with patients rating 18 QL items on a five-point scale. RESULTS: Most respondents (74%) were 55 to 74 years old, had early stage disease at diagnosis (81%) and were diagnosed within 2 years of the survey (81%). The top five rated issues were: overall QL, ability to perform normal activities, maintaining independence, ability to sleep, and not being a burden. These items were ranked as either “very important” or “important” by at least 88% of patients. None of the most highly ranked issues were symptoms. Instead, the highest ranked items were global issues reflecting the impact of symptoms on patients. In addition to the enhanced content validity findings, good reliability results and initial support for construct validity are reported for the PCSS. CONCLUSIONS: This is the largest survey providing patient-expressed background for content validity for QL and PRO measures. The findings of this study should aid development of newer practical questionnaires, such as the PCSS, which can be adapted to electronic platforms enhancing rapid and accurate PRO and QL evaluation.